A Qualitative Approach to the Use of Digital Modules in Teaching Argumentative Essay Writing to University Students - Hasibuan, Siti Aminah (FKIP Unismuh Makassar, 2025)
This study investigates the use of digital modules as a pedagogical tool in teaching argumentative essay writing to university students, using a qualitative research approach. The research aims to examine how digital learning materials enhance students’ understanding of argumentative structures, improve writing skills, and support autonomous learning. This study employed a qualitative research methodology to explore how digital modules are used in teaching argumentative essay writing to university students. A qualitative approach was deemed appropriate for capturing the lived experiences, perceptions, and challenges encountered by both students and instructors in an authentic educational setting. Data were gathered through classroom observations, in-depth interviews with students and instructors, and analysis of students' written work. The findings suggest that digital modules provide structured and accessible content that aids students in organizing their ideas, developing critical arguments, and refining their writing techniques. Additionally, the interactive nature of digital modules fosters student engagement and motivation. Despite some challenges related to technical access and digital literacy, the overall impact of using digital modules in writing instruction is perceived as positive. In conclusion, digital modules can serve as effective scaffolding mechanisms that guide students through the complexities of argumentative writing. When designed with clear instructional sequences, examples, and interactive components, digital modules help students understand essay structure, develop coherent arguments, and engage in independent revision.